Characteristic and resource potential of water soluble lithium in lithium-rich salt lake sediments from Qaidam Basin, China - Zhe Ma; Xiuzhen Ma; Dan Ma; Yubin Li; Xin Liu; Guojing Zhu; Qi Wei; Yunqi Ma; Syed Hussain Asim; Lu Cong (PLoS ONE, 2025)
This study investigates geochemical characteristics and resource potential of water-soluble lithium in lithium-rich salt lake sediments from the Qaidam Basin, focusing on the East Taijinar Salt Lake and Bieletan area. Through X-ray diffraction (XRD), elemental analysis (ICP-OES), and laser particle size analysis (LPSA), sediment samples were analyzed to assess mineral composition, lithium distribution and its occurrence forms. Results reveal distinct vertical zonation: lithium, boron, and potassium peak in clay-rich layers, contrasting with lower concentrations in halite-dominated layers. Regional patterns indicate that lithium enrichment in sediments aligns closely with brine, centered around Yiliping and East/West Taijinar Salt Lakes. Water-soluble lithium primarily originates from weak adsorption on clay minerals, with secondary contributions from intercrystalline brine, halite fluid inclusions, and gypsum dissolution. The clay layers exhibit lithium concentrations exceeding industrial grade and favorable Mg/Li ratios, comparable to brine mining standards. Co-enrichment of boron (415 ppm) and potassium highlights multi-resource potential. These findings highlight sediments as lithium reservoirs, which can serve as a sustainable potential supplement during brine depletion and enhance resource resilience in the Qaidam Basin. This study provides critical insights into lithium migration, enrichment mechanisms, and strategic resource management in evaporitic systems.